ANALISIS VALIDASI PENGEMBANGAN MODEREN PADA SISWA TUNAGRAHITA DI SLB SISWA BUDHI, SURABAYA - Pradana, Febryansah Gilang Aris (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
This research is an activity process to produce MODEREN (Motoric Development of Special Children) learning models which are developed to train motoric skills of mild mentally retarded children. The devices developed are modification tools and circuit learning methods. But in this writing focused on the process of validation testing through the construct test and the contents of the development tools made. The validators involved in this study were 5 people, namely Dr. Nanik Indahwati, M.Or. experts in the field of motor learning. Dr. Dwi Cahyo Kartiko. S.Pd., M.Kes. experts in the field of adaptive sports education. Andhega Wijaya S.Pd. Jas M.Or. experts in the field of learning media. Dra. Hj. Siti Mahmudah, M.Kes. experts in the field of social psychology and orthopedagogics of mentally retarded children. Drs. Edy Rianto, M.Pd. experts in penjas and adaptive sports. The final results of this study are MODEREN tools and models that are specifically for mild mentally retarded children to practice valid student motor skills.